PENATALAKSANAAN PENCABUTAN GIGI DENGAN KONDISI SISA AKAR (GANGREN RADIK) - Yuwono, Budi (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2010)
One of dental treatments on gangrene radix is an extraction. However, tooth extraction on the chronic gangrene radix needs particular procedure since this condition frequently emerges periapical disorder like dental granuloma or radicular cyst. Both dental granuloma and radicular cyst may rest and grow to be jaw cyst leading to the damage of jawbone although the causing tooth has already been removed. The procedure of tooth extraction with chronic gangrene radix covers extraction accompanied with enucleation and curettage of periodontal tissue using both close method and open method